AdipoR1 enhances the radiation resistance via ESR1/CCNB1IP1/cyclin B1 pathway in hepatocellular carcinoma cells - Yuhan Gan; Linhui Zhu; Yimo Li; Ruoting Ge; Jiahe Tian; Yuxin Chen; Xiang He; Shumei Ma; Xiaodong Liu (Molecular Medicine)
Abstract Hepatocellular carcinoma is one of the most common malignant tumors, and radiotherapy plays a pivotal role in its therapeutic regimen. However, radiotherapy resistance is the main cause of therapeutic failure in patients. Our previous study revealed that Adiponectin Receptor 1 (AdipoR1) is involved in regulating radiation resistance in liver cancer patients treated with stereotactic body radiotherapy. To explore the mechanism, we performed high-throughput transcriptome sequencing of hepatocellular carcinoma cells with stable knockdown of AdipoR1. KEGG enrichment analysis indicated that the cell cycle and ubiquitination degradation pathways may be involved in the regulation of radiation resistance by AdipoR1.The knockdown of AdipoR1 can attenuate the radiation-induced G2/M phase arrest through cyclin B1.By the ubiquitination IP assay and a rescue experiment, we confirmed that CCNB1IP1 regulated the ubiquitination and degradation of cyclin B1. Combined with information from transcription factor database and AdipoR1 transcriptome sequencing, these results showed that estrogen receptor 1 (ESR1) may be a transcription factor of CCNB1IP1. We found that AdipoR1 promoted the translocation of ESR1 from the cytoplasm to the nucleus, and ESR1 inhibited the transcription of CCNB1IP1.Therefore, we propose that AdipoR1 regulates the ubiquitination level, cell cycle progression, and radiation resistance of HCC cells through the “AdipoR1 /ESR1/CCNB1IP1/cyclin B1” axis. This study will promote the development of novel targeted radiosensitizing drugs.